2023
DOI: 10.22495/cbsrv4i2art13
|View full text |Cite
|
Sign up to set email alerts
|

Stimulating achievements: The mediating effect of employee commitment between high-performance work practices and employee engagement

Abstract: Drawing on the social exchange paradigm, this study evaluated the mediating effects of employee commitment (EC) in the relationship between high-performance work practices (HPWP) and employee engagement (EE) in Nigeria. The study used the social exchange theory and this paradigm has been previously used in the works of Blau (1964), Gouldner (1960), and Settoon et al. (1996). The study adopts a cross-sectional survey research design via questionnaire administration. Three employee engagement (vigor, dedication … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Employees' relations show that a strong association exists between HRM policies, employees' attitudes and performance (Guest, Michie, Sheehan &Metochi, 2020). That's why Arubayi & Odiri, (2023) suggested that in order for organizations' achievement to be stimulated, there is the need to put in place mechanisms aimed at making employees more dedicated and engaging them in the decision-making process. HRM policies are the primary means via which organizations can influence and shape the skills, attitudes, and behaviour of employees to do their work and thus achieve organizational goals (Collins & Clark, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Employees' relations show that a strong association exists between HRM policies, employees' attitudes and performance (Guest, Michie, Sheehan &Metochi, 2020). That's why Arubayi & Odiri, (2023) suggested that in order for organizations' achievement to be stimulated, there is the need to put in place mechanisms aimed at making employees more dedicated and engaging them in the decision-making process. HRM policies are the primary means via which organizations can influence and shape the skills, attitudes, and behaviour of employees to do their work and thus achieve organizational goals (Collins & Clark, 2019).…”
Section: Introductionmentioning
confidence: 99%